Newborn screening for sickle cell disease in Europe: recommendations from a Pan‐European Consensus Conference. (18th October 2018) - Lobitz, Stephan; Telfer, Paul; Cela, Elena; Allaf, Bichr; Angastiniotis, Michael; Backman Johansson, Carolina; Badens, Catherine; Bento, Celeste; Bouva, Marelle J.; Canatan, Duran; Charlton, Matthew; Coppinger, Cathy; et al.
Summary: Sickle Cell Disease (SCD) is an increasing global health problem and presents significant challenges to European health care systems. Newborn screening (NBS) for SCD enables early initiation of preventive measures and has contributed to a reduction in childhood mortality from SCD. Policies and methodologies for NBS vary in different countries, and this might have consequences for the quality of care and clinical outcomes for SCD across Europe. A two‐day Pan‐European consensus conference was held in Berlin in April 2017 in order to appraise the current status of NBS for SCD and to develop consensus‐based statements on indications and methodology for NBS for SCD in Europe. More than 50 SCD experts from 13 European countries participated in the conference. This paper aims to summarise the discussions and present consensus recommendations which can be used to support the development of NBS programmes in European countries where they do not yet exist, and to review existing programmes.